PENGEMBANGAN TEMPAT WISATA DAN KULINER SAUNG ENDE SEBAGAI UPAYA PENINGKATAN EKONOMI MASYARAKAT SEKITAR - Agung Julkarnaen; Mukhsin Al Hosin; Nanda Fitria; Ade Fauji (Yayasan Education and Social Center, 2026)
Saung Ende is a growing tourism and culinary destination located in Waringinkurung District, Serang Regency, BantenProvince. This community service research aims to describe the condition and potential of Saung Ende as a tourism and culinary destination, analyze its economic impact on the surrounding community, and identify obstacles and opportunities in its development. The research employs a descriptive qualitative approach using in-depth interviews and field observation as the main data collection methods. Three informants participated: Bapak Taufik (50 years old) as the manager of Saung Ende, Ibu Bulan (23 years old) as a visitor, and Bapak Indra (26 years old) as a visitor who also sampled the culinary offerings. Data were analyzed using the Miles and Huberman interactive model through data reduction, data display, and conclusion drawing. Results show that Saung Ende possesses significant natural and cultural tourism potential, characterized by an authentic rural atmosphere, traditional Sundanese-Banten culinary offerings, and scenic natural surroundings. The presence of Saung Ende has generated positive economic impacts for the local community through local employment absorption, increased income for traders, and stimulation of micro-enterprises in the surrounding area. However, several challenges persist, including infrastructure limitations, minimal digital promotion, and suboptimal tourism management. This research recommends strategies encompassing facility improvement, digital marketing optimization, development of integrated tourism packages, and strengthening of human resource capacity.